2016
DOI: 10.1080/2162402x.2016.1254856
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 inhibitors in multiple myeloma: The present and the future

Abstract: The introduction of PD-1/PD-L1 pathway inhibitors has marked a significant milestone in the treatment of various types of solid tumors. The current situation in multiple myeloma (MM) is rather unclear, as distinct research groups have reported discordant results. This discrepancy dominantly concerns the expression of PD-1/PD-L1 molecules as well as the identification of the responsible immune effector cell population. The results of monotherapy with PD-1/PD-L1 inhibitors have been unsatisfactory in MM, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 53 publications
0
37
0
1
Order By: Relevance
“…Anti‐PD‐1 mAbs are represented mainly by nivolumab (OPDIVO, MDX1106, BMS‐936558; Bristol‐Myers Squibb, New York City, NY, USA) – a fully human IgG4 mAb; pembrolizumab (KEYTRUDA, MK‐3475; Merck, Kenilworth, NJ, USA) – a highly selective humanized IgG4 mAb and pidilizumab (MDV9300, CT‐011; Medivation/Pfizer, New York City, NY, USA) – an IgG1 mAb. Within the anti‐PD‐L1 mAbs, the most promising are durvalumab (Celgene, Summit, NJ, USA) and atezolizumab (Roche, Basel, Switzerland), which have just entered the early phases of clinical testing …”
Section: Introductionmentioning
confidence: 99%
“…Anti‐PD‐1 mAbs are represented mainly by nivolumab (OPDIVO, MDX1106, BMS‐936558; Bristol‐Myers Squibb, New York City, NY, USA) – a fully human IgG4 mAb; pembrolizumab (KEYTRUDA, MK‐3475; Merck, Kenilworth, NJ, USA) – a highly selective humanized IgG4 mAb and pidilizumab (MDV9300, CT‐011; Medivation/Pfizer, New York City, NY, USA) – an IgG1 mAb. Within the anti‐PD‐L1 mAbs, the most promising are durvalumab (Celgene, Summit, NJ, USA) and atezolizumab (Roche, Basel, Switzerland), which have just entered the early phases of clinical testing …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PD-L1 is expressed on plasma cells but also on DC in the bone marrow, with a various intensity of PDL-1 expression among patients. [13][14][15][16]21 Furthermore, PD-L1-expressing pDC are increased and localized with PD-L1-positive MM cells in bone marrow. 19 Importantly, PD-L1 expression correlates with progression of disease, with the highest levels of expression in relapsed or relapsed/refractory MM.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Chen et al demonstrated that CD38 upregulation in tumors induces resistance to PD‐1/PD‐L1 blocking antibodies and coinhibition of CD38 and PD‐L1 improves antitumor immune response. Several studies have shown that PD‐L1 is expressed on plasma cells but also on DC in the bone marrow, with a various intensity of PDL‐1 expression among patients . Furthermore, PD‐L1‐expressing pDC are increased and localized with PD‐L1‐positive MM cells in bone marrow .…”
Section: Discussionmentioning
confidence: 99%
“…183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions. 200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide. 221-224 In line with preclinical and clinical data demonstrating that multi-epitope vaccines are generally more powerful than their single-epitope counterparts, 117,225 the most common vaccination strategy employed by these studies consists in targeting simultaneously multiple TAAs (20 studies).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%